Role of cell block preparation in neoplastic lesions - Basnet, S; Talwar, OP (Journal of Pathology of Nepal, 2012)
Background: Fine needle aspiration cytology of superficial lesion or deep anatomical site is an increasingly common procedure in diagnosis of neoplastic lesions. Sometimes fine needle aspiration does not yield sufficient information for precise diagnosis and the risk of false negative or intermediate diagnosis always exists. In order to overcome these problems, cell block technique has been resorted to make the best use of available material. Materials and Methods:This was a prospective hospital based study conducted in the department of pathology, Manipal Teaching Hospital, Pokhara, Nepal over a period of 2 years from the year 2009 October to 2011. There were total of 49 cases included in the study of which fine needle aspiration cytology smears, cell block and biopsy specimens were available. Results: A total of 49 such cases were included in the study of which fine needle aspiration cytology smears, cell block and biopsy specimens were available. Of all the malignant cases, 12 cases were from lungs aspirate, 10 were from breast, 15 from lymph node and 12 from thyroid. With the combined use of smear and cell block, the diagnostic accuracy of the tumors approaches 100% and also significantly improves diagnostic and sub typing accuracy of malignancies. Cell blocks were found superior in diagnosing neoplasm than smears with diagnostic accuracy of 95.91% and 91.8% respectively. Conclusion: Cell block method allows the recovery and processing of minute amounts of cellular material and facilitates the better classification of tumor when reviewed along with cytological smears. The method is simple to perform and no expertise is required to handle the specimen. Therefore the routine preparation of the cell block improves the accuracy of fine needle aspiration cytology diagnosis. Journal of Pathology of Nepal (2012) Vol. 2, 272-276 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6876